Prevalence of Iron Deficiency Anemia Amongst Patients Infected with Helicobacter Pylori at Tertiary Care Hospital - Amjad Hussain, Muhammad Nadeem, Radhia Khan, Muhammad Khalid, Komal Iqbal, Muhammad Ishfaq, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Anemia is a worldwide public health issue, prevalent in both industrialized and developing nations. In recent studies, an infection with H. pylori has been linked to a variety of hematological problems like iron and vitamin B12 deficiencies. Objective: To find out the prevalence of iron deficiency anemia amongst patients infected with helicobacter pylori Methodology: The current study was cross-sectional carried out at the department of medicine, Qazi hussain Ahmad Medical Complex for duration of one year from 20-July 2020 to 30-July 2021. To determine the iron deficiency anemia, blood samples were taken from all the patients and sent to the concerned laboratory of the hospital for the required diagnostic tests. All the analysis of data was done by using IBM SPSS version 23. Results: In this study totally 100 patients were included. There were 48 (48%) males and 52 (52%) females’ patients. The mean age in the current study was 39.11 (±10.12) years. Overall, iron deficiency anemia was observed in 35 (35%) patients. Based on the stratification of iron deficiency anemia with age and gender, no significant association was observed (p˃0.05). Conclusion: Our study concludes that the prevalence of iron deficiency anemia amongst patients infected with helicobacter pylori is high. Our study recommends screening of all iron deficiency anemia patients of unknown cause for helicobacter pylori infection. Keywords: Iron deficiency anemia; Helicobacter pylori; Infection